GRAMMATICAL ERRORS IN INDONESIAN-ACEHNESE EFL LEARNERS’ DESCRIPTIVE ESSAYS - Zulfikar Zulfikar (Journal of English Education and Linguistics, 2020)
This study was carried out to analyze the types and the sources of grammatical errors encountered in Acehnese EFL learners’ essays. It focused on finding out the most dominant type of errors and the most plausible explanation for the source of errors the students made in their writing. Twenty (20) learner’s essays were collected to be analyzed by referring to Azar’s error classification as well as Richard’s theory on learners’ sources of the errors. The results showed that the most frequent type of errors in the learners’ essays were incomplete sentences and verb tenses, making up more than a third (36.7%) of the total 392 errors. The findings also showed intralingual errors are the major causes of the learners’ grammatical errors, followed by interference errors and developmental errors respectively. The findings suggest that in teaching essay writing, teachers of Indonesian-Acehnese EFL learners need to adopt and devise more appropriate techniques in both grammar and writing instructions, focusing on complete sentence structure and tenses in order to minimize the possible errors made by the learners in their writing.